CAPSICUM (Capsicum annuum var. grossum L.) RESPONSE TO DIFFERENT N AND K FERTIGATION LEVELS ON YIELD, YIELD ATTRIBUTES AND WATER PRODUCTIVITY UNDER POLY HOUSE - K. AVIL KUMAR; V. RAMULU, B. GOUTHAMI, M. UMA DEVI K. AVIL KUMAR and (The Journal of Research, PJTSAU, 2021)
Capsicum (Capsicum annuum var.grossum L.) also referred to as sweet or bell pepper is a highly priced vegetable crop both in the domestic and international market. It is a cool season crop occupying an area of 32 thousand hectares, producing 493 thousand metric tonnes in India. In Telangana it occupies an area of 150.2 ha, with 2873 metric tonnes production (Telangana State Horticulture Mission, 2018-19). The major capsicum producing states in India are Himachal Pradesh, Karnataka, Madhya Pradesh, Haryana, Jharkhand, Uttarakhand and Orissa. Capsicum is a member of Solanaceae family, native to tropical South America and was introduced in India by the Portuguese in the middle of sixteenth century.